A review of the essential visual skills required for field hockey: beyond 20-20 optometry - Sneyimani, T.; Mathenjwa, M.; Millard, L.; Breukelman, G. J. (Asian Journal of Sports Medicine, 2023)
Context: Field hockey is a very technical and tactical sport, requiring immense levels of visual concentration on moving and stationary targets, which can improve visual and team performance. However, in literature, this area of specialty remains underutilized, with most studies seeking to improve physical and physiological performance. Essential visual skills cannot only be attributed to field hockey but to other ball-playing sports and activities of daily living, which allow humans to coexist. The essential visual skills reduce the propensity of making poor decisions, ill preparations, and the exclusion of potent and capable players. Objectives: This review novelly aims to not only compile a comprehensive list of essential visual skills for field hockey players but also to create a starting point for future studies to add to this list, to aid in player talent identification, and eventually create sport-specific visual exercise programs and testing batteries. Discussion: The skills identified in this review preface a platform for human performance professionals to include in their training regimens, with an intent to maximize performance and talent identification and to aid in the formulation of visuospatial test batteries. Even though this list is comprehensive, this is only a starting point for future research to find more visual skills that are essential to field hockey, as well as provide the opportunity to develop the performance of the visual skills of these athletes in ways that have not been done before.